Inbound Marketing Strategy “BNI Tapcash” in the Competition of Electronic Money as a Digital Payment Tool - Purwati, Retno; Melati, Inaya Sari (Universitas Negeri Semarang, 2022)
This study aimed to determine the inbound marketing strategy of PT Bank Negara Indonesia TapCash. This study used a qualitative method with data collection through interviews with the head of the consumer business division of the card section, managers of digital operations, marketing, and customers of Bank Negara Indonesia. The data analysis technique used SWOT analysis so that internal and external factors could be found. Based on the results of data analysis, the inbound marketing strategy implemented by PT Bank Negara Indonesia to market TapCash had four strategies, namely posting blogs, SEO, advertising and networking, while the inbound marketing strategy that used email had not been applied to TapCash marketing and based on the SWOT analysis,it showed that the strategy inbound marketing in TapCash marketing got quite profitable results because of the greater strength and opportunity factors although the strengths and opportunities generated were not too large compared to the weaknesses and threats, but this was enough to help increase the use of TapCash cards because with an increase in the number of advertisements could increase also the number of transactions and TapCash users.